Restoration of Elbow Flexion With a Free Functional Gracilis Muscle Transfer in an Arthrogrypotic Patient Using a Motor Nerve to Pectoralis Major. (September 2020) - Sochol, Kristen M.; Edwards, George; Stevanovic, Milan
Background: Patients with arthrogryposis may exhibit inability to flex the elbow. A free functional gracilis muscle transfer (FFGMT) can be used to restore elbow flexion. In our search of the available literature, we have not seen any descriptions of using a motor branch to the pectoralis major as a donor nerve to establish elbow flexion.Methods: We performed an FFGMT for restoration of elbow flexion in an arthrogrypotic patient with no active elbow flexion, who had a Medical Research Council (MRC) muscle grade of 0.Results: We report our 4.5-year outcomes. After undergoing an FFGMT for elbow flexion, our patient was able to gain an MRC grade 4 and achieve an arc of motion of 25° to 140°.Conclusion: An FFGMT for elbow flexion may be performed successfully using a motor branch to the pectoralis major.